Optimization of the conditions for the formation and cryopreservation of compatible spheroids of rat mesenchymal stem cells and neural cells - Maiorova, Olga; Sukach, Oleksandr; Ochenashko, Olga; Vsevolodska, Svitlana (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):234